2019
DOI: 10.1002/bjs5.50248
|View full text |Cite
|
Sign up to set email alerts
|

Topical moistening of mastectomy wounds with diluted tranexamic acid to reduce bleeding: randomized clinical trial

Abstract: Background Topical administration of tranexamic acid (TXA) may be an alternative to intravenous administration to reduce bleeding with a lower risk of systemic adverse events. The aim of this study was to investigate whether moistening a surgical wound with TXA before closure, leaving a thin film of drug only, would reduce postoperative bleeding. Methods This was a two‐centre, stratified, parallel‐group, placebo‐controlled, double‐blind RCT. Patients undergoing mastectomy with or without axillary lymph node cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 33 publications
3
35
0
4
Order By: Relevance
“…Notably, TXA was also found to be superior to steroids use in the prevention of bleeding [56]. Regarding studies on topical/local use of TXA, Ausen et al reported that topical application of TXA in mastectomy procedures was associated with a reduction in postoperative bleeding as measured by drain output in the first 24 h after surgery [49,58]. However, in the same study, the rate of seroma trended towards being higher in the TXA group, although not reaching statistical significance.…”
Section: Aesthetic Surgery/breast Surgerymentioning
confidence: 94%
See 3 more Smart Citations
“…Notably, TXA was also found to be superior to steroids use in the prevention of bleeding [56]. Regarding studies on topical/local use of TXA, Ausen et al reported that topical application of TXA in mastectomy procedures was associated with a reduction in postoperative bleeding as measured by drain output in the first 24 h after surgery [49,58]. However, in the same study, the rate of seroma trended towards being higher in the TXA group, although not reaching statistical significance.…”
Section: Aesthetic Surgery/breast Surgerymentioning
confidence: 94%
“…Tranexamic acid is the most popular anti-fibrinolytic used in aesthetic surgery [48]. In our review, 23 studies assessed the use of TXA in various aesthetic or breast-related procedures [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64]. [57,59,60], and one was a case series [52].…”
Section: Aesthetic Surgery/breast Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…The same author 33 published a similar 2-center, double-blinded, randomized clinical trial to investigate the effect of this moistening method but in 202 patients who underwent either simple mastectomy or mastectomy with sentinel node biopsy, or mastectomy with axillary lymph node clearance. The method of administration and doses was identical to those of the previous study.…”
Section: Breast Surgerymentioning
confidence: 99%